2018
DOI: 10.21037/jtd.2018.06.70
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node upstaging for non-small cell lung cancer after uniportal video-assisted thoracoscopy

Abstract: Background: Radical lymph node dissection (LND) plays a major role in the treatment of non-small cell lung cancer (NSCLC). This study presents the analysis of the results after uniportal video-assisted thoracoscopy (VATS) lymphadenectomy during anatomical lung resections for NSCLC, focusing on pathological nodal upstaging. Any possible risk factor affecting nodal upstaging was also investigated. Methods: The prospectively collected clinical data of 136 patients undergone uniportal VATS anatomical lung resectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…However, lymph node dissection can be related to postoperative morbidity, which is low but may occur due to bleeding, recurrent nerve paralysis, esophageal wounds, chylothorax, aggravation of bronchial congestion by pulmonary denervation, and bronchial fistula by devascularization of the stump [ 8 ]. Furthermore, routine pathological analysis techniques using hematoxylin-eosin-saffron (HES) staining can lead to the omission of up to 20 to 30% of micrometastases [ 9 , 10 , 11 , 12 ]. The lack of detection of these occult micrometastases can be responsible for an understaging of the disease, and most studies have found that lymph node micrometastases could adversely affect the prognosis of NSCLC patients [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, lymph node dissection can be related to postoperative morbidity, which is low but may occur due to bleeding, recurrent nerve paralysis, esophageal wounds, chylothorax, aggravation of bronchial congestion by pulmonary denervation, and bronchial fistula by devascularization of the stump [ 8 ]. Furthermore, routine pathological analysis techniques using hematoxylin-eosin-saffron (HES) staining can lead to the omission of up to 20 to 30% of micrometastases [ 9 , 10 , 11 , 12 ]. The lack of detection of these occult micrometastases can be responsible for an understaging of the disease, and most studies have found that lymph node micrometastases could adversely affect the prognosis of NSCLC patients [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The number of retrieved nodes predictive of pathological upstaging is also an argument of debate among the authors. Ismail and colleagues [ 15 ] concluded that the resection of 18 nodes could be the best predictor of general nodal upstaging (13.3%) in a single-centre VATS series of 136 patients and suggested the removal of at least seven nodes from hilar stations and eleven from mediastinal ones to enhance the possibilities of detecting an unforeseen nodal disease.…”
Section: Discussionmentioning
confidence: 99%
“…Ismail et al (28) showed how, in the hands of expert U-VATS surgeons, the mean number of lymph nodes retrieved during U-VATS lobectomy can be satisfactory (20.14 ± 10.73) and comparable to the mean reported in the literature for other techniques (13.42 ± 8.24 in Triportal-VATS, 9.44 in open surgery, 17 in RATS), as well as the incidence of nodal upstaging (13.3% in U-VATS vs. 6.7-12.8% reported in other approaches). In particular, the pN1-upstaging (7.4%) and pN2-upstaging (3%) were also in line with the literature (27).…”
Section: Minimally-invasive Lndmentioning
confidence: 99%